RNA binding protein with multiple splicing (RBPMS) promotes contractile phenotype splicing in human embryonic stem cell-derived vascular smooth muscle cells. - Jacob, Aishwarya G; Moutsopoulos, Ilias; Petchey, Alex; Kollyfas, Rafael; Knight-Schrijver, Vincent R; Mohorianu, Irina; Sinha, Sanjay; Smith, Christopher WJ (Oxford University Press (OUP), 2024)
AIMS: Differentiated vascular smooth muscle cells (VSMCs) express a unique network of mRNA isoforms via smooth muscle-specific alternative pre-mRNA splicing (SM-AS) in functionally critical genes, including those comprising the contractile machinery. We previously described RNA Binding Protein with Multiple Splicing (RBPMS) as a potent driver of differentiated SM-AS in the rat PAC1 VSMC cell line. What is unknown is how RBPMS affects VSMC phenotype and behaviour. Here, we aimed to dissect the role of RBPMS in SM-AS in human cells and determine the impact on VSMC phenotypic properties. METHODS AND RESULTS: We used human embryonic stem cell-derived VSMCs (hESC-VSMCs) as our platform. hESC-VSMCs are inherently immature, and we found that they display only partially differentiated SM-AS patterns while RBPMS protein levels are low. We found that RBPMS over-expression induces SM-AS patterns in hESC-VSMCs akin to the contractile tissue VSMC splicing patterns. We present in silico and experimental findings that support RBPMS' splicing activity as mediated through direct binding and via functional cooperativity with splicing factor RBFOX2 on a significant subset of targets. We also demonstrate that RBPMS can alter the motility and the proliferative properties of hESC-VSMCs to mimic a more differentiated state. CONCLUSION: Overall, this study emphasizes a critical role for RBPMS in establishing the contractile phenotype splicing programme of human VSMCs.
Keywords: Alternative splicing; RNA-binding proteins; Vascular smooth muscle; Humans; Human Embryonic Stem Cells; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; RNA Splicing Factors; Phenotype; Cell Differentiation; RNA-Binding Proteins; Alternative Splicing; Cell Proliferation; Vasoconstriction; Cell Line; Repressor Proteins